The natural development and trainability of plyometric ability during childhood - Lloyd, R. S.; Meyers, R. W.; Oliver, J. L. (Strength and Conditioning Journal, 2011)
The inclusion of plyometrics within youth-based strength and conditioning programs is becoming more popular as a means to develop stretch-shortening cycle ability. Plyometric training adaptations have previously been reported for running velocity, power, agility, and running economy, and therefore, athletes should be exposed to this training modality at some point during their training program. However, some uncertainty still exists with regard to program design, especially when taking growth and maturational factors into account. This article reviews the current youth-based plyometric literature and provides a training progression model based around the long-term development of young athletes.